2009
DOI: 10.1016/j.cell.2009.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Ligands Dll4 and Jagged1 Have Opposing Effects on Angiogenesis

Abstract: The Notch pathway is a highly conserved signaling system that controls a diversity of growth, differentiation, and patterning processes. In growing blood vessels, sprouting of endothelial tip cells is inhibited by Notch signaling, which is activated by binding of the Notch receptor to its ligand Delta-like 4 (Dll4). Here, we show that the Notch ligand Jagged1 is a potent proangiogenic regulator in mice that antagonizes Dll4-Notch signaling in cells expressing Fringe family glycosyltransferases. Upon glycosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,018
6
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 964 publications
(1,095 citation statements)
references
References 50 publications
48
1,018
6
4
Order By: Relevance
“…Dll4 is usually upregulated by vascular endothelial growth factor in endothelial tip cells, which possess high Dll4 and low Notch (Patel et al, 2005;Hofmann and Luisa Iruela-Arispe, 2007;Benedito et al, 2009). The enhanced Dll4 could activate Notch in the adjacent stalk cells, which exhibit high Notch and low Dll4 (Hofmann and Luisa Iruela-Arispe, 2007;Phng and Gerhardt, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Dll4 is usually upregulated by vascular endothelial growth factor in endothelial tip cells, which possess high Dll4 and low Notch (Patel et al, 2005;Hofmann and Luisa Iruela-Arispe, 2007;Benedito et al, 2009). The enhanced Dll4 could activate Notch in the adjacent stalk cells, which exhibit high Notch and low Dll4 (Hofmann and Luisa Iruela-Arispe, 2007;Phng and Gerhardt, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…2). Interestingly, endothelial cell-specific Dkk-2 Tg mice display a vascular phenotype similar to Jag-1 Tg mice (74), and Jag-1 promotes Dkk-2 expression through Notch in human small intestine stem cells (75). These results imply that Dkk-2 might regulate angiogenic activity of endothelial cells through crosstalk with Notch signaling.…”
Section: Dickkopf-2mentioning
confidence: 88%
“…The mechanism behind the extension/formation of the new vasculature has been a recent subject of intense interest and has led to development of VEGF inhibitors for antiangiogenic tumor therapies. Recent studies have also unveiled the pivotal importance of Notch signaling in the process of angiogenesis, with specific focus on 2 Notch ligands DLL4 and JAG1 (5,(38)(39)(40)(41)(42). It is suggested that branching of new vasculature is a result of modulation of Notch signaling within the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%